Exploring the impact of performance-based high-intensity treadmill training in chronic stroke patients: a group-matched, single-blind pilot trial with a 3-month follow-up - Lee, Hye-Jin; Oh, Duck-Won (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. In recent years, the beneﬁts of treadmill training for patients with post-stroke hemiparesis have been increasingly recognised, particularly with the incorporation of higher training speeds tailored to patients’ performance levels. This study aimed to investigate the eﬀects of performance-based high-intensity treadmill training on balance and walking in patients with chronic stroke.Methods. With the allocation of participants based on location convenience, 20 patients with chronic stroke were assigned to either the experimental group (n1 = 10), which underwent performance-based high-intensity treadmill training at a pace individually ad-justed according to their walking ability, or the control group (n2 = 10), which underwent treadmill training at a self-selected speed. The intervention was conducted twice daily for 5 days over a 2-week period, with a follow-up measurement taken 3 months after the intervention. Balance function was measured using the Berg Balance Scale and Activity-Speciﬁc Balance Conﬁdence Scale, and walking function was assessed using the 10-metre walk test and 6-minute walk test.Results. After the intervention, participants in the experimental group showed signiﬁcantly greater improvements in all variables compared to participants in the control group (p < 0.05). Gains in walking variables were maintained at the 3-month follow-up (p < 0.05).Conclusion. These ﬁndings suggest that performance-based high-intensity treadmill training may be a beneﬁcial intervention to enhance balance and walking functions in patients with post-stroke hemiparesis.
Keywords: performance-based speed; physical training; hemiparesis; balance; walking